2015
DOI: 10.1186/s13075-015-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative interaction of functional inflammasome genetic variants in determining the risk of gout

Abstract: IntroductionThe acute gout flare results from a localised self-limiting innate immune response to monosodium urate (MSU) crystals deposited in joints in hyperuricaemic individuals. Activation of the caspase recruitment domain-containing protein 8 (CARD8) NOD-like receptor pyrin-containing 3 (NLRP3) inflammasome by MSU crystals and production of mature interleukin-1β (IL-1β) is central to acute gouty arthritis. However very little is known about genetic control of the innate immune response involved in acute go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 59 publications
2
55
3
Order By: Relevance
“…This study identified that CARD8 rs2043211 was not associated with increased gout risk, which is in contrast to the known difference of genetic distribution of this SNP in the Chinese and European gout population (67). As far as we know, this study is the first to determine genetic association between the P2X7R SNP and gout patients, revealing that P2X7R polymorphism did not increase the risk of gout in our study population.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This study identified that CARD8 rs2043211 was not associated with increased gout risk, which is in contrast to the known difference of genetic distribution of this SNP in the Chinese and European gout population (67). As far as we know, this study is the first to determine genetic association between the P2X7R SNP and gout patients, revealing that P2X7R polymorphism did not increase the risk of gout in our study population.…”
Section: Discussioncontrasting
confidence: 79%
“…Although the precise pathogenic mechanism of gout has not been clearly determined, several crucial proteins such as the purinergic receptor P2X ligand-gated ion channel 7 ( P2X7R ) (345) and caspase activation and recruitment domain 8 ( CARD8 ) (67) proteins are known to be responsible for the pathogenesis of gout.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified polymorphisms in the NALP3 inflammasome, TLR-4, CARD8, IL-1β, IL-18, and CD14 genes to be associated with gout [30–35]. A cross sectional study examining genetic association in European and Maori New Zealanders and Caucasian controls found a significant multiplicative interaction between polymorphisms in the CARD8 and IL-1β genes and gout, further supporting the role of a pro-inflammatory genotype in gout pathogenesis [33]. Thus, further studies are required to understand if these genetic changes explain the propensity for developing recurrent gout attacks, and for gout attacks to be triggered by pro-inflammatory dietary and lifestyle factors.…”
Section: Discussionmentioning
confidence: 81%
“…A variant in TLR4 , that likely influences TLR4 expression, has been associated with gout in two studies 97,98. Two SNPs in NLRP3-related genes have been associated with gout 99101. The first one is a nonsense variation in the caspase recruitment domain-containing protein 8 (CARD8, rs2043211 ), a negative regulator of the NLRP3 inflammasome.…”
Section: Mechanistic Aspects Of Abcg2 In Inflammationmentioning
confidence: 99%